Learning literature: undergraduates’ views, experiences, and academic achievement - Jamiah Baba; Shireena Basree Abdul Rahman; Radzuwan Ab Rashid (Journal of Education and Learning (EduLearn), 2026)
The paper explores the debate over incorporating literature into English as a second language (ESL) classrooms, underscoring the importance of addressing learners’ expectations and interests. Emphasising learners’ expectations and interests not only enhances engagement but also fosters a deeper appreciation for language nuances, cultural contexts, and diverse perspectives embedded within literary works. Therefore, the study aims to understand learners’ perspectives and challenges in learning literature, and assesses the impact on their literature academic achievements. The study utilised a quantitative approach that involved seventy pre-service teaching English as a second language (TESL) teachers enrolled in several literature courses. A questionnaire with multiple-choice and open-ended questions were used to gather relevant data, and responses were analysed using frequency counts and cross-tabulations. The academic grades of the learners were analysed and cross-tabulated with the questionnaire items. Overall, learners expressed positive views of literature, enjoying the learning process and emphasising the need for scaffolding and support in understanding the literature texts covered. These findings suggest implications for educators in planning and delivering literature courses, shaping how ESL learners engage with literature.